We Grow Accustomed to the Light - Minh Q Nguyen (HCA Healthcare Journal of Medicine, 2026)
Drawing inspiration from Emily Dickinson’s exploration of the unknown in "We Grow Accustomed to the Dark," this poem, "We Grow Accustomed to the Light," re-examines the final transition of life through a clinical and humanist lens. While Dickinson focused on the bravery required to navigate the "Dark," this piece explores the courage needed to face the "Light," representing the clarity of terminal illness, the shedding of medical "fetters," and the shared experience of the "final goodbye." It challenges the traditional medical impulse to "push forward" at all costs, instead advocating for a "Wise" acceptance of the natural end of the human journey. This poem serves as a reflection on palliative peace and the role of the clinician as a lantern-bearer for patients and their families.